2020
DOI: 10.1108/dpm-05-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Addressing capacities of local communities in a changing context in Nepal

Abstract: PurposeThe field study aimed at exploring how capacities are influenced by external factors in the context of community-based disaster risk reduction (CBDRR).Design/methodology/approachThe field study was conducted in a small rural area called Lapsibot in Lamjung district in Nepal. The article is based on a fieldwork conducted in April 2018. The different tools of data collection were inspired by the vulnerability and capacity assessment approach with a focus on various aspects of vulnerabilities and capacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In a health context, for example, this extends to looking at why are vulnerable populations worst affected or affected differently and how can everyone have access to healthcare in such a setting. Taking an example from a different disaster, during the post-earthquake (2015) zones of Nepal in February 2019, it became evident how difficult it is to reach many areas, given the difficult terrain and landscape of the landlocked country (Pyda et al 2019 ; Rolsted & Raju 2020 ). Health is not a stand-alone sector and access to healthcare is influenced by many factors that arise from sociopolitical, economic and cultural dimensions.…”
mentioning
confidence: 99%
“…In a health context, for example, this extends to looking at why are vulnerable populations worst affected or affected differently and how can everyone have access to healthcare in such a setting. Taking an example from a different disaster, during the post-earthquake (2015) zones of Nepal in February 2019, it became evident how difficult it is to reach many areas, given the difficult terrain and landscape of the landlocked country (Pyda et al 2019 ; Rolsted & Raju 2020 ). Health is not a stand-alone sector and access to healthcare is influenced by many factors that arise from sociopolitical, economic and cultural dimensions.…”
mentioning
confidence: 99%
“…This included the young and elderly, who were curious and interested in the activity that had been set up in a public space (the main square "Praça Dr Oswaldo Cruz"). They were the first group we interacted with because we wanted to consider different available resources and knowledge from the community to respond to disasters (Rolsted and Raju, 2020). Thus, we did not restrict the group to specific demographic and socioeconomic conditions, but instead we chose to make this session more like an ice-breaker activity.…”
Section: Methodsmentioning
confidence: 99%
“…Nepal is faced with landslides and floods every year and vulnerability remains a constant problem. Therefore, disaster risk reduction will not be effective with only disaster preparedness that does not address the root causes of vulnerability and lack of capacities 48 . This conclusion can also be drawn when looking at the heat wave in parts of India and Pakistan 28 which has shown that the same vulnerable populations and many others affected disproportionately during COVID-19 are also affected during the heatwave.…”
Section: The Disasters Of 2021/22mentioning
confidence: 99%